Władza i słuszność w narracji biblijnej - ROSHWALD, Mordecai; MIKULSKA, Patrycja (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2013)
The confrontation of Might and Right is one of the basic themes of the Bible. Indeed, the imperative of commitment to Right and the belief in its vindication can be considered to be a major contribution of the Israelite civilization to the Western creed. The present essay explores this theme in some Biblical stories – such as that of Joseph and the tale of the exodus from Egypt – where it is not obvious. The paper also highlights this major theme in some other narratives, where the issue is explicitly articulated. Yet, the belief in the vindication of Right is challenged in the Bible itself, as well as in post-Biblical literature, in the face of Israelite (Jewish) and universal human experience. An indirect response to such challenge is implied in eschatological prophecy and in messianic beliefs, which envisage a perfect world of universal peace and justice.